Learning media for making electrical circuits using electronic workbench - Hutagalung, Siti Nurhabibah; Panjaitan, Melda (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Computer media in the teaching and learning process in the classroom, can solve learning problems, namely, changing student learning patterns to be more effective by increasing knowledge and skills and can increase student motivation and ultimately can enhance student learning outcomes. EWB (Electronic Work Bench) is a type of electronic software used to simulate the workings of an electrical circuit. The need for electrical circuit simulation is to test whether the electrical circuit can run properly and in accordance with the theoretical approach used in electronic books, without having to make the electrical circuit in reality. The availability of minimal supporting learning media hinders the creation of effective learning activities so that the research team uses Electronic Workbench media in designing electronic components with targeted success. Students at Budi Darma University gave enthusiastic responses to this training seen from the number of student attendance and their response during the training and were able to understand electronic design, able to assemble simple electronic components using Electronic Workbench.